IDENTIFIKASI POTENSI EKONOMI KAWASAN GAMBUT DI DESA PETANANG, KECAMATAN KUMPEH, KABUPATEN MUARO JAMBI - Muryati, Sri; Rahmatia, Citra; Tamtomo, Hario (LPPM Universitas Muhammadiyah Jambi, 2023)
The peatland have holds enormous potential, but also very complex problems. The complexity is caused by the fragile characteristics of peatlands and the many interests of peatland. The management of peatland, which are often drained for use as agricultural land and residential areas, results in land subsidence. Dry peat is a good fuel, so excessive drying of land can cause land and forest fires to easily occur. Management of peat areas requires selection of suitable tree species for planting, knowledge of specific silvicultural techniques in peat areas, less fertile (nutrient-poor) peat swamp habitat and high acidity so that plants generally have slow growth. The purpose of this study was to obtain data on regional potential related to peatland management techniques in Petanang Village, Muaro Jambi. As well as getting a community based management model on the potential in the area. The results of the identification of economic potential in the peat areas of Petanang Village are expected to provide viable alternative livelihood options to gradually reduce pressure on peatlands, as well as build community capacity in developing economic activities from the proper use of peatlands.